Is Sadness Only One Emotion? Psychological and Physiological Responses to Sadness Induced by Two Different Situations: “Loss of Someone” and “Failure to Achieve a Goal” - Shirai, Mariko; Suzuki, Naoto (Frontiers in Psychology, 2017)
We investigated whether sadness elicited by two different situations―loss of someone (loss) and failure to achieve a goal (failure)―had different physiological responses. Seventy-four participants were randomly assigned to one of three conditions (loss, failure, and neutral). Physiological responses were recorded during an imagery task that was designed to evoke sadness. The results of characteristics in the subjective ratings indicated that loss-evoked sadness was only associated with expressive words relating to tears. For the results of physiological measures, skin conductance levels increased during the imagery task across all conditions and differed between conditions during the post-task. For the loss condition, restoration to baseline level took longer, while in the failure the skin conductance level decreased sharply back to baseline. Furthermore, tear ratings correlated with blood pressures in the loss condition, while sadness intensity correlated with blood pressures in the failure condition. These results suggest that sadness includes at least two subtypes that produce different responses in subjective ratings and physiological measures.